Analisis Perbedaan Tekanan Darah Pada Akseptor Pengguna Kontrasepsi Suntik Depo Medroxyprogesterone Acetate - Ardiyani Istiwardani; Nurmainah Nurmainah; Ressi Susanti (Journal Syifa Sciences and Clinical Research, 2022)
The most widely used contraceptive method in controlling the Indonesian population is a three-month injection KB called Depo Medroxyprogesterone Acetate. Three-month injection KB has a side effect in the form of an increase in blood pressure in the acceptor of the user. The purpose of this study was to analyze the average blood pressure of acceptors and to analyze the relationship between duration of use of DMPA injectable contraceptives and the increase in blood pressure of DMPA injectable contraceptive acceptors at the Pontianak City Health Center. The method used in this research is an analytic observational study with a cohort research design. Sampling was done by purposive sampling, namely sampling based on inclusion and exclusion criteria. Data analysis was performed using univariate (microsoft excel) and bivariate with Chi-square analysis. The results showed an increase in the average blood pressure in the age group of 9.9-10.5 mmHg (systolic) and 3.7-6.2 mmHg (diastolic). The average increase in blood pressure in the long-term use group was 9.2-10.7 mmHg (systolic) and 3.0-5.3 mmHg (diastolic). Chi-square analysis showed that there was no relationship between duration of use and the risk of hypertension in acceptors of DMPA injection contraceptive users at the Pontianak City Health Center (p = 0.176; RR = 1.582; 95% CI = 0.795-3.149)